2019
DOI: 10.1093/cercor/bhz180
|View full text |Cite
|
Sign up to set email alerts
|

The Cortical Organization of Syntax

Abstract: Syntax, the structure of sentences, enables humans to express an infinite range of meanings through finite means. The neurobiology of syntax has been intensely studied but with little consensus. Two main candidate regions have been identified: the posterior inferior frontal gyrus (pIFG) and the posterior middle temporal gyrus (pMTG). Integrating research in linguistics, psycholinguistics, and neuroscience, we propose a neuroanatomical framework for syntax that attributes distinct syntactic computations to thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
188
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 237 publications
(256 citation statements)
references
References 220 publications
27
188
4
Order By: Relevance
“…This work provides the first evidence in acute stroke of a functional and anatomical dissociation between temporal-parietal and frontal focal brain regions for lexically and syntactically driven processes required for spontaneous connected speech. These results are consistent with predictions from models of syntactic processing based primarily on evidence from language comprehension (Friederici et al, 2017;Hagoort, 2019;Matchin and Hickok, 2019;cf. Wilson et al, 2016;Fedorenko et al, 2018;Rogalsky et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This work provides the first evidence in acute stroke of a functional and anatomical dissociation between temporal-parietal and frontal focal brain regions for lexically and syntactically driven processes required for spontaneous connected speech. These results are consistent with predictions from models of syntactic processing based primarily on evidence from language comprehension (Friederici et al, 2017;Hagoort, 2019;Matchin and Hickok, 2019;cf. Wilson et al, 2016;Fedorenko et al, 2018;Rogalsky et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Thothathiri et al, 2012;Magnusdottir et al, 2013;Blank et al, 2016;Wilson et al, 2016;Fedorenko et al, 2018;Rogalsky et al, 2018). Matchin and Hickok (2019) propose that the inherently different processing requirements for language production and comprehension account for the differences in syntactic processing related neural substrates. In production as well as comprehension, the generation of lexicalsemantic structure is required both to understand the relationship between words during comprehension, as well specify relationships between words to accurately reflect the message to be produced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified patients' grammatical deficits through a perceptual rating of patients' speech samples. According to the hypothesis presented in Matchin & Hickok (2019), we expected a double dissociation: paragrammatism would be associated with damage to the pMTG (and not IFGtri) while agrammatism would be associated with damage to IFGtri (and not the pMTG). Because neuroimaging studies have also identified syntactic effects in neighboring tissue (see Matchin & Hickok, 2019 for a review), and the difficulty of straightforwardly interpreting the localization in lesion-symptom mapping (Wilson, 2016), we created broader regions of interest (ROIs) encompassing these regions in order to maximize our ability to detect effects.…”
Section: Introductionmentioning
confidence: 97%
“…An important issue concerning research into syntactic deficits in aphasia is the question of how syntax is organized in the healthy brain. While prominent models of syntax in the brain posit a primary syntactic function to different subregions of the inferior frontal gyrus (Friederici 2017;Hagoort 2014), Matchin and Hickok (2019) recently hypothesized a new model of syntax in the brain, with two primary cortical zones responsible for distinct aspects of syntactic processing. The first is a hierarchical lexical-syntactic system in the left posterior middle temporal gyrus (pMTG), including the ventral bank of the superior temporal sulcus (STS).…”
Section: Introductionmentioning
confidence: 99%